Analysis of soluble interleukin-2 receptor as CSF biomarker for neurosarcoidosis. Issue 4 (July 2020) - Otto, Carolin; Wengert, Oliver; Unterwalder, Nadine; Meisel, Christian; Ruprecht, Klemens
Abstract : Objective: To systematically analyze soluble interleukin-2 receptor (sIL-2R) in CSF as a diagnostic and disease activity biomarker in patients with sarcoidosis involving the CNS (neurosarcoidosis). Methods: sIL-2R was determined by chemiluminescent immunoassays in CSF/serum samples from patients with neurosarcoidosis (n = 23), MS (n = 19), neurotuberculosis (n = 8), viral (n = 18) and bacterial (n = 9) meningitis, cerebral lymphoma (n = 15), Guillain-Barré syndrome (n = 8), and 115 patients with noninflammatory neurologic diseases (NINDs) as controls. The sIL-2R index was calculated by dividing the CSF/serum sIL-2R quotient (QsIL-2R ) through the CSF/serum albumin quotient (QAlb ). sIL-2R quotient diagrams were established by plotting QsIL-2R against QAlb . sIL-2R levels were correlated with clinical, MRI, and CSF disease activity markers of neurosarcoidosis. Results: Patients with neurosarcoidosis had higher CSF sIL-2R, QsIL-2R, and sIL-2R index values than patients with NINDs ( p < 0.0001 for all pairwise group comparisons). sIL-2R quotient diagrams demonstrated an intrathecal sIL-2R synthesis in >50% of neurosarcoidosis samples. Similar findings were observed in viral/bacterial meningitis, CNS lymphoma, and, most pronounced, in neurotuberculosis, but not in patients with MS. CSF sIL-2R parameters were associated with clinical disease activity, leptomeningeal gadolinium enhancement, and the CSF white cell count in patients with neurosarcoidosis. Conclusions: CSF sIL-2R parameters are elevated in patients with neurosarcoidosis, but this finding is not specific for neurosarcoidosis. Nevertheless, CSF sIL-2R parameters may help distinguishing neurosarcoidosis from MS and are associated with clinical, radiologic, and CSF disease activity markers of neurosarcoidosis. Classification of evidence: This study provides Class II evidence that CSF sIL-2R parameters distinguish neurosarcoidosis from NINDs and MS.